Estudio de Factibilidad para el diseño de un sistema hidropónico de lechuga en Parcelas de San Carlos del municipio de Villavicencio (2024)
The main objective of this degree work is to carry out a feasibility study for the design of a hydroponic lettuce system in the Parcel of San Carlos in the municipality of Villavicencio. The project is focused on the production of fresh hydroponic lettuce in the city of Villavicencio and aims to determine how feasible it is to produce this type of cold climate food, because the city does not have optimal climatic conditions for the production of This vegetable is so important in the diet of the people of the city.